Depiction of Lord Vishnu on the external walls of the Antarala - Temples of India Project Team (Jio Institute, 2024)
The external walls of the antarala (vestibule or antechamber) of the Sitaleshwar Temple are decorated with beautiful sculptures of deities. On the rear (west) wall, Lord Vishnu is depicted seated on a pedestal in lalitasana (the royal position or position of royal ease). He is presented with four arms, carrying a gada (mace), a chakra (discus), and a shankha (conch shell). His front right hand is posed in abhayahasta (hand pose indicating reassurance or protection from fear). He is depicted wearing a crown with a halo around his head.